Riding the Padel Wave: How Content Marketing Shapes Gen Z’s FOMO and JOMO Through the Bandwagon Effect - Dian Indah Suari, Ni Putu; Iswari Pidada, Ida Ayu (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to examine the influence of content marketing on FOMO (Fear of Missing Out), JOMO (Joy of Missing Out), and the Bandwagon Effect, which serves as a mediating variable affecting Generation Z’s participation in the padel sports trend in Denpasar City. The research employed a quantitative survey method by distributing online questionnaires to 140 respondents belonging to Generation Z residing in Denpasar City. The collected data were analyzed using SmartPLS 4. The results show that content marketing has a positive and significant effect on FOMO and the Bandwagon Effect, while its influence on JOMO is relatively weak and insignificant. The Bandwagon Effect also has a positive impact on both FOMO and JOMO and acts as a mediator that strengthens the effect of content marketing on FOMO. The research model explains approximately 65% of the variation in endogenous variables. The findings indicate that Generation Z in Denpasar City is more influenced by the fear of missing out (FOMO) than by the joy of missing out (JOMO) in the context of padel sports. Therefore, sports marketing strategies should emphasize emotional, social, and social validation aspects in content creation to effectively encourage participation.